Nutrition knowledge in athletes: A systematic review - Heaney, S.; O`Connor, H.; Michael, S.; Gifford, J.; Naughton, G. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
Nutrition education aims to enhance knowledge and improve dietary intake in athletes. Understanding athletes` nutrition knowledge and its influence on dietary intake will inform nutrition-education programs in this population. Purpose: To systematically review the level of nutrition knowledge in athletes, benchmark this against nonathlete comparison groups, and determine the impact of nutrition knowledge on dietary intake. Methods: An extensive literature search from the earliest record to March 2010 using the terms nutrition knowledge or diet knowledge and athlete or sport was conducted. Included studies recruited able or physically disabled, male or female, competitive (recreational or elite) athletes over the age of 13 yr. Quantitative assessment of knowledge and, if available, diet intake was required. Because of variability in the assessment of nutrition knowledge and dietary intake, meta-analysis was not conducted. Results: Twenty-nine studies (17 published before 2000) measuring nutrition knowledge (7 including a nonathlete comparison group) met inclusion criteria. Athletes` knowledge was equal to or better than that of nonathletes but lower than comparison groups including nutrition students. When found statistically significant, knowledge was greater in females than males. A weak (r < .44), positive association between knowledge and dietary intake was reported in 5 of 9 studies assessing this. Common flaws in articles included inadequate statistical reporting, instrument validation, and benchmarking. Conclusion: The nutrition knowledge of athletes and its impact on their dietary intake is equivocal. There is a need for high-quality, contemporary research using validated tools to measure nutrition knowledge and its impact on dietary intake.